Poroelastic effects associated with earthquakes on overpressured reverse and normal faults - Marguin, Valentin; Simpson, Guy (Frontiers in Earth Science, 2024)
Earthquakes in fluid-saturated rocks induce sudden changes in pore-pressures that can lead to appreciable postseismic deformation. However, earthquakes can also release fluids from overpressured parts of the crust, which can also contribute to additional postseismic effects. In this study, we use two-dimensional poroelastic models to investigate postseismic deformation and fluid pressures following ruptures on overpressured dip-slip faults that slide according to rate- and state-dependent friction. We show that when the crust prior to rupture has pore pressures in hydrostatic equilibrium, then ruptures induce fluid pressure anomalies according to the field of coseismic elastic volumetric strain. These pore pressure anomalies relax with time to produce characteristic postseismic deformation that depends on the slip magnitude and fault style, as typically observed. However, very different results are obtained if the crust is appreciably overpressured at the time an earthquake is nucleated. In this case, the poroelastic response is overwhelmingly dominated by drainage and fluid pressure drop within the overpressured crust, which is facilitated by an increase in permeability on the fault during rupture. This results in transient postseismic subsidence that occurs irrespective of the faulting style, fault geometry, slip magnitude or details of the coseismic strain field. The time scale and magnitude of this postseismic subsidence are controlled by the magnitude of the fluid overpressure prior to rupture, the maximum coseismic permeability and how rapidly the fault permeability recovers following an earthquake. The poroelastic effects associated with rupturing of overpressured faults may be at least an order of magnitude greater that the classic poroelastic response (i.e., relaxation of pore pressures generated by coseismic elastic volumetric strain). Overall, our results highlight the potentially dramatic effect that the breaching of deep overpressured fluid reservoirs can have on fluid pressures and surface displacements following earthquakes.